Microalgae Biodiversity: Sustainable Biofactories for Food, Fuel and Therapeutics - Sanchez, Libertine Rose S.; Monotilla, Wilberto D. (Diliman Review; Vol 66 No 2 (2022), 2024)
Microalgae refers to diverse range of microscopic algae that are of great economic, biomedical, environmental, industrial and agricultural resources for all life forms. Applied phycology is a promising field making use of the microalgae biodiversity as a response to the needs of times: food, green fuel and therapeutics resources. These photosynthetic prokaryotic cyanobacteria and eukaryotic microalgae are regarded as sustainable biofactories because of their great capability to convert dioxide and nutrients into biomass. The high composition and concentration of valuable metabolites in these microalgae mitigate our current demands for functional foods as needed by both animals and humans, nutrition and health therapeutics as well as bio-energy resources. Genomics and genetic engineering along with morphometric and biochemical characterization are being used to analyze their metabolic pathways in order to improve their lipid synthesis and biomass accumulation. Arthrospira platensis , Haematococcus pluvialis , Porphyridium sp., Chlamydomonas reinhardtii and Nostoc sp. dominate the biomass production in open and closed system photobioreactors. They are in high demand as food, feeds, nutraceuticals, bioactive metabolite sources for antimicrobial, antiviral and antitumor treatments, bio-oil and biodiesel sources. This mini-review paper might spur the interest of Asian industries to establish microalgae production since most photobioreactors are in European and American countries.